METALINGUISTIC KNOWLEDGE AT PLAY: USING COMMON CORE EN ESPAÑOL TO DEVELOP TEACHING-SPECIFIC SPANISH COMPETENCIES IN BILINGUAL TEACHER EDUCATION IN THE U.S.A. - Aquino-Sterling, Cristian R. (Instituto Tecnológico de Costa Rica, 2015)
The present article describes how “Common Core en Español” (CC-E) standards can be employed as didactic resources for facilitating the development of teaching-specific (professional) Spanish competencies in bilingual teacher education. After describing the U.S. context of CC-E, and addressing the language and metalinguistic demands these new standards denote for K-12 students and teachers, the author provides a description of a content-based and task-based instructional activity implemented in a bilingual teacher education course he designed and facilitated. The activity served to develop future bilingual teachers’ metalinguistic knowledge (difference between the Spanish “diptongo” and “hiato”) and functional teaching-specific Spanish competencies (explanation of the main differences between the metalinguistic concepts outlined). The article then focuses on the analysis of a written student response resulting from the activity. It concludes by outlining curricular and pedagogical implications for developing professional Spanish competencies in bilingual teacher education within a U.S. context.